Tunable femtosecond nonlinear absorption and optical limiting thresholds of La2O3‒B2O3 glasses by controlling the borate structural units. (1st April 2022) - Jagannath, G.; Gaddam, Anuraag; Rao, S. Venugopal; Agarkov, D.A.; Korableva, G.M.; Ghosh, Manasi; Dey, Krishna Kishor; Ferreira, José M.F.; Allu, Amarnath R.
Abstract: Utilization of optical limiting materials to suppress the input intense laser energy is obligatory in a wide variety of applications that deploy the high‒power laser sources. In this letter, we demonstrate that the optimization of borate structural units in lanthanum borate (LB) glasses through the addition of various concentrations of heavy metal oxides (HMOs) (PbO and Bi2 O3 ) resulting in achievement of an optimum optical threshold value. The structural changes of these glasses were analyzed by 11 B MAS‒NMR and Raman spectroscopic techniques. Nonlinear optical attributes were assessed by the Z‒scan technique. The enhancement of two‒photon absorption coefficient and decrement in optical limiting threshold factors suggest the LB glasses containing HMOs could be beneficial for power optical limiting devices. The achieved optical limiting threshold values of 0.075 and 0.114 J/cm 2 at 700 and 800 nm, respectively, are superior compared to advanced materials such as nanoparticles, carbon nanotubes, and few‒layers of MoS2 /Polymethylmethacrylates. Graphical abstract: Image, graphical abstract